2014
DOI: 10.1103/physrevlett.113.144101
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Synchronization of Complex Networks

Abstract: We study optimal synchronization in networks of heterogeneous phase oscillators. Our main result is the derivation of a synchrony alignment function that encodes the interplay between network structure and oscillators' frequencies and can be readily optimized. We highlight its utility in two general problems: constrained frequency allocation and network design. In general, we find that synchronization is promoted by strong alignments between frequencies and the dominant Laplacian eigenvectors, as well as a mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
207
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(218 citation statements)
references
References 33 publications
10
207
1
Order By: Relevance
“…where L ij = δ ij k i − A ij is the combinatorial Laplacian whose presence in such fluctuation problems is wellknown [17]. Multiplying by the cos λ i gives a weighted version of the Laplacian.…”
Section: Static Kuramoto-sakaguchi Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…where L ij = δ ij k i − A ij is the combinatorial Laplacian whose presence in such fluctuation problems is wellknown [17]. Multiplying by the cos λ i gives a weighted version of the Laplacian.…”
Section: Static Kuramoto-sakaguchi Systemmentioning
confidence: 99%
“…To understand the basic properties of the local Kuramoto-Sakaguchi model we repeat the steady state solution considered for the global case, such as in [17]. We consider solutions of the form…”
Section: Static Kuramoto-sakaguchi Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies coming from different fields suggest that, apart from structure, there may be other important factors defining and shaping network dynamics [28,29,57,85]. For example, it has been shown that models of spiking neural networks [25-27, 34,35,40] may exhibit specific spike patterns which may be generated by any network from a high-dimensional family of networks.…”
Section: Parametrization Of Network Dynamicsmentioning
confidence: 99%